Exploring Relationships: A Systematic Review on Intimate Partner Violence and Attachment - Velotti, Patrizia; Beomonte Zobel, Sara; Rogier, Guyonne; Tambelli, Renata (Frontiers in Psychology, 2018)
Background: Intimate Partner Violence (IPV) is an important public health challenge. In recent years, there has been a greater awareness concerning this phenomenon, its causes and consequences. Due to the relational nature of IPV, attachment theory (Bowlby, 1988) appears a useful framework to read the phenomenon and to better understand its components and its dynamics to provide more precise and tailored interventions in the future. Purpose: To summarize our knowledge of the research concerning IPV and attachment with an aim to better design and implement future research. Methods: Computer database researches were conducted using the following databases: Psychinfo, Psycharticle, Medline, Scopus, Web of Science and PubMed (all years to the 01/02/2018). Search terms were compiled into two concepts for all database namely Attachment and IPV. Results: After removing the duplicates, a total of 3598 records was screened, resulting in the identification of 319 full-text articles to be further scrutinized. Upon closer examination, there was consensus that 113 of those studies met the study inclusion criteria. Data was organized considering specifically studies concerning 1) IPV victimization and attachment, 2) IPV perpetration and attachment (both these sections were articulated in Physical, Psychological and Sexual IPV), and 3) New research (comprising same-sex couples, IPV and attachment in couple contexts and IPV profiles and attachment among perpetrators). Conclusion: A number of studies failed to find significant associations between insecure attachment and IPV victimization or perpetration. Additional research is needed to provide a greater understanding of different IPV forms and to aid in the development of prevention and treatment interventions.